The effect of work culture and work environment on employee loyalty through work stress as a media variable at PT.OMFI - Puti Amalina; Hery Winoto Tj; Melitina Tecoalu (Institute of Computer Science (IOCS), 2023)
Employee loyalty is an important issue faced by companies because loyalty is the mental attitude shown by employees towards the company. This study aims to determine the influence of work culture and work environment on employee loyalty, the influence of work culture and work environment on employee work stress, the influence of work stress on employee loyalty, as well as the influence of work culture and work environment on employee loyalty through work stress. The population in this study consists of all 623 permanent employees of PT. omfi. The sampling technique used in this study was non-probability sampling, specifically purposive sampling. The sample for this study consisted of 90 employee respondents from PT. omfi. The research results indicate that work culture has a significant effect on employee loyalty, while the work environment does not have a significant effect on employee loyalty. Work culture significantly influences employee work stress, and the work environment also has a significant impact on employee work stress. Work stress significantly affects employee loyalty. Furthermore, the work culture and the work environment both have a significant influence on employee loyalty at PT. OMFI through work stress.